2022
DOI: 10.3390/jpm12020135
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Oncology Multidisciplinary Tumor Board: The Point of View of the Neuroradiologist

Abstract: Background: The multi-disciplinary tumor board (MTB) is essential to quality cancer care and currently recommended to offer the best personalized clinical approach, but little has been published regarding MTBs in neuro-oncology (nMTBs). The aim of the present paper is to describe our nMTB, to evaluate its impact on clinical management decisions, and to assess the role of neuroradiologists. Methods: The retrospective evaluation of the cases discussed at our nMTB from March 2017 to March 2020. From the electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Still, the vast majority of those patients were able to complete the standard adjuvant treatment. This observation relativizes the importance of plain numbers; though the KPS score and age are important prognostic parameters, indication for surgery in fragile patients should be decided by the multidisciplinary brain tumor board, as routinely happens at our institution [ 6 ]. During the multidisciplinary meeting, the patient’s clinical history is thoroughly illustrated by the referral physician, and all possible therapeutic options are evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the vast majority of those patients were able to complete the standard adjuvant treatment. This observation relativizes the importance of plain numbers; though the KPS score and age are important prognostic parameters, indication for surgery in fragile patients should be decided by the multidisciplinary brain tumor board, as routinely happens at our institution [ 6 ]. During the multidisciplinary meeting, the patient’s clinical history is thoroughly illustrated by the referral physician, and all possible therapeutic options are evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In oncology, tumor boards have been established as a means of improving accuracy in diagnosis, bettering adherence to clinical guidelines, advancing the integration of novel research and clinical trials in clinical management, and improving patient outcomes [ 76 ]. Prior studies have demonstrated that multidisciplinary tumor boards improve both the quality of medical services offered to patients as well as OS rates [ 77 , 78 , 79 , 80 ].…”
Section: Optimizing Management Of Cns Metastases Across a Health Care...mentioning
confidence: 99%
“…Although brain cancers exhibit a wide range of neoplasms, including limited or metastatic forms, the standard treatment commonly includes surgery, chemotherapy, radiotherapy, and immunotherapy. Chemotherapy for CNS cancers is still regarded as one of the most challenging treatments in the clinic (Gaudino et al, 2022; Ghajar‐Rahimi et al, 2022; H. S. Kim & Lee, 2022; Koekkoek et al, 2023; Lutz et al, 2022). Despite new anticancer drug developments in recent years, the prognosis for brain cancer patients, particularly those with malignant tumors, has remained poor (Koekkoek et al, 2023).…”
Section: Introductionmentioning
confidence: 99%